ENVIRONMENTAL SECURITY THREATS DUE TO CLIMATE CHANGE FACED BY THE PACIFIC ISLAND FORUM - Ardita Tazya Nuraini; M. Syaprin Zahidi (Kajian Asia Pasifik, 2023)
Climate change has a detrimental impact on living things, including humans. Starting from extreme weather changes, rising sea levels, disasters, and the worst thing is that it can sink the island which is home to several humans and other living things. Climate change is a disaster that should be prevented from getting worse. The Pacific Islands are one of the few areas that are threatened with drowning due to rising sea levels every year. With the various interests held by developed countries, especially in the industrial sector, of course, letting the Pacific Islands sink in without any action for change is a crime.